Cubital Tunnel Syndrome - Modern Treatment Options - Aleksandra Sieradzka; Krzysztof Szerej; Alicja Kot; Marta Wojtczak; Natalia Myśliwiec; Adrian Różycki; Michał Pniak; Paweł Miklis; Maciej Mawlichanów; Aleksandra Ciesielska (Quality in Sport)
Introduction: Cubital Tunnel Syndrome (CuTS) is the second most prevalent compression neuropathy affecting the upper extremity. Patients typically present with symptoms of paresthesia in the fourth and fifth digits, accompanied by hand weakness and pain. Most patients respond well to conservative treatments, but some of them require surgical intervention.